2016
DOI: 10.1186/s12974-016-0475-0
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomes derived from atorvastatin-modified bone marrow dendritic cells ameliorate experimental autoimmune myasthenia gravis by up-regulated levels of IDO/Treg and partly dependent on FasL/Fas pathway

Abstract: Background: Previously, we have demonstrated that spleen-derived dendritic cells (DCs) modified with atorvastatin suppressed immune responses of experimental autoimmune myasthenia gravis (EAMG). However, the effects of exosomes derived from atorvastatin-modified bone marrow DCs (BMDCs) (statin-Dex) on EAMG are still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…Immature bone marrow DCs are able to secrete tolerogenic exosomes, which are involved in the suppression of immune responses in a rat model of experimental autoimmune myasthenia gravis. These EVs upregulate levels of IDO/Treg and decrease synthesis of anti‐R97‐116 IgG, IgG2a and IgG2b antibodies [170]. Moreover, DC‐derived EVs can mediate the activation of CD4 + T cells through an endocrine mechanism, leading to improved cardiac function and wound healing after myocardial infarction [171].…”
Section: ‘Theranostic’ Applications Of Immune Cell‐derived Evsmentioning
confidence: 99%
“…Immature bone marrow DCs are able to secrete tolerogenic exosomes, which are involved in the suppression of immune responses in a rat model of experimental autoimmune myasthenia gravis. These EVs upregulate levels of IDO/Treg and decrease synthesis of anti‐R97‐116 IgG, IgG2a and IgG2b antibodies [170]. Moreover, DC‐derived EVs can mediate the activation of CD4 + T cells through an endocrine mechanism, leading to improved cardiac function and wound healing after myocardial infarction [171].…”
Section: ‘Theranostic’ Applications Of Immune Cell‐derived Evsmentioning
confidence: 99%
“…Beside analyses of their protein cargo, EVs have been reported to carry DNA or distinct RNAs and they are able to transfer genetic information from cell to cell ( 20 26 ). Thus, EVs are increasingly recognized as mediators of intercellular communication ( 27 – 30 ), and their role in the pathogenesis of autoimmune diseases or tumor growth has been discussed ( 3 , 31 36 ). However, while the EV field is rapidly expanding, there is an urgent need to better define vesicle subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that dendritic cell-derived exosomes (DEXs) deliver antigen-specific signals and can be regarded as inert vehicles that mimic DCs and activate T cells [16]. The biological function of DEXs in tumors and inflammatory diseases has been demonstrated in a number of studies [17-19]. However, to our knowledge, there have been no studies investigating the biological function of DEXs in liver I/R or whether DEXs can modulate CD4+ T cell activation and differentiation.…”
Section: Introductionmentioning
confidence: 99%